Pengaruh Persepsi Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Konsumen Di Tomoro Coffee Di Warakas Jakarta Utara - Naufal Rafianis Syafiq; Sukirno (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.The purpose of this study is to understand how consumer perceptions of product quality and priceinfluence their purchasing decisions, and to identify the extent of the collective influence of these twofactors. This study uses a descriptive method with a quantitative approach, namely examining the statusof a group of people, an object, a thought, or a class. The population and sample used by the researcherwere all consumers of Tomoro Coffee Warakas, North Jakarta, with 320 respondents. The results showthat perceived product quality has a positive and significant influence on purchasing decisions by 41.2%.Similarly, perceived price also has a positive and significant influence on purchasing decisions by 28.9%.Simultaneously, these two variables contribute 51.4% to purchasing decisions, while the remaining48.6% is influenced by other factors not examined. These findings indicate that good product qualityand the perception of an appropriate price significantly influence the purchasing decisions of TomoroCoffee consumers in Warakas, North Jakarta. Therefore, companies need to consistently maintainproduct quality and adjust prices to remain competitive in order to increase consumer loyalty and repeatpurchase decisions.Keywords: Product Quality, Price, Purchase Decisions, Coffee, Consumers